2012
DOI: 10.1038/oby.2012.59
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Induced by Chronic Dapagliflozin Treatment Is Attenuated by Compensatory Hyperphagia in Diet‐Induced Obese (DIO) Rats

Abstract: Dapagliflozin is a potent and selective sodium glucose cotransporter‐2 (SGLT2) inhibitor which promotes urinary glucose excretion and induces weight loss. Since metabolic compensation can offset a negative energy balance, we explored the potential for a compensatory physiological response to the weight loss induced by dapagliflozin. Dapagliflozin was administered (0.5–5 mpk; p.o.) to diet‐induced obese (DIO) rats with or without ad libitum access to food for 38 days. Along with inducing urinary glucose excreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
159
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(185 citation statements)
references
References 30 publications
22
159
3
1
Order By: Relevance
“…Although substantial progress has been achieved in preclinical studies, the putative success and safety of coagonist therapy for the treatment of patients with obesity and T2DM remains uncertain and requires extensive additional clinical validation 110 . Another potential future option is a SGLT-2 inhibitor/GLP1-RA combination in an attempt to weaken the compensatory "overeating" mechanism observed with SGLT-2 inhibition 91 .…”
Section: Peptide Hormone Combination Therapiesmentioning
confidence: 99%
“…Although substantial progress has been achieved in preclinical studies, the putative success and safety of coagonist therapy for the treatment of patients with obesity and T2DM remains uncertain and requires extensive additional clinical validation 110 . Another potential future option is a SGLT-2 inhibitor/GLP1-RA combination in an attempt to weaken the compensatory "overeating" mechanism observed with SGLT-2 inhibition 91 .…”
Section: Peptide Hormone Combination Therapiesmentioning
confidence: 99%
“…Although increased glucose excretion contributes to the weight loss observed with SGLT2 inhibitor treatment, weight reduction is often limited to ,4 kg after even 52 weeks of treatment (55). This attenuation of weight loss may occur because SGLT2 inhibitor-induced glycosuria is accompanied by compensatory hyperphagia, as demonstrated in animal studies (63) and suggested by human studies (64,65 59 kg) (55,66). When used in combination therapy, dapagliflozin and canagliflozin were associated with an increased risk of genital tract infections, whereas dapagliflozin was also associated with a modest increased risk of UTI.…”
Section: Sodium-glucose Cotransporter 2 Inhibitorsmentioning
confidence: 99%
“…However, it is obvious that strict carbohydrate restriction up-regulates lipolysis and ketogenesis. Similarly, the administration of an SGLT-2 inhibitor, which enhances urinary glucose excretion, resulted in a carbohydrate shortage and increased ketogenesis in rats [33]. Therefore, ketogenesis has a greater physiological and pathological effect on patients with a low-carbohydrate diet and those who are given SGLT-2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%